Traditional uses of medicinal plants used by Indigenous communities for veterinary practices at Bajaur Agency, Pakistan - Muhammad Abdul Aziz; Amir Hasan Khan; Muhammad Adnan; Habib Ullah (BMC, 2018)
Abstract Background The pastoral lifestyle of Indigenous communities of Bajaur Agency is bringing them close to natural remedies for treating their domestic animals. Several studies have been conducted across the globe describing the importance of traditional knowledge in veterinary care. Therefore, this study was planned with the aim to record knowledge on ethnoveterinary practices from the remote areas and share sit with other communities through published literature. Methods Data was gathered from community members through semi-structured interviews and analyzed through informant consensus factor (Fic) to evaluate the consent of current ethnoveterinary practices among the local people. Results In total, 73 medicinal plants were recorded under the ethnoveterinary practices. Most widely used medicinal plants with maximum use reports (URs) were Visnaga daucoides Gaertn., Foeniculum vulgare Mill., Solanum virginianum L., Withania somnifera (L.) Dunal, Glycyrrhiza glabra L., and Curcuma longa L. New medicinal values were found with confidential level of citations for species including Heracleum candicans and Glycerhiza glabra. Family Apiaceae was the utmost family with high number (7 species) of medicinal plants. Maximum number of medicinal plants (32) was used for gastric problems. High Fic was recorded for dermatological (0.97) followed by reproductive (0.93) and gastrointestinal disorders (0.92). The main route of remedies administration was oral. Conclusions Current study revealed that the study area has sufficient knowledge on ethnoveterinary medicinal plants. This knowledge is in the custody of nomadic grazers, herders, and aged community members. Plants with new medicinal uses need to be validated phytochemically and pharmacologically for the development of new alternative drugs for veterinary purposes.